Determinants of satisfaction based on library service quality - Aprih Santoso (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2020)
Testing the effect of library service quality on satisfaction with library facilities as a moderating variable will be the aim of this study. The population of this study was the students of Economics Faculty University of Semarang Academy Year 2019/2020. All members of the population have homogeneous properties so that researchers use non-probability convenience sampling technique with 100 students. The method of analysis : validity test, reliability twst, heterocedasticity test, normality test, multicollinearity test, coefficient of determination (R²), hypothesis test, MRA (Moderated Regression Analysis) test and linear regression models.The results of study are the variable quality of library services have a positive and significant effect on satisfaction. Variable library facility significantly strengthen the positive relationship between of library services quality on satisfaction.